Two degree of freedom plotter using robotic arm - Hanafi, Muhammad Muaz; Bhuiyan, Moinul (2014)
This research is related to the mechanism of a development of two degree of freedom plotter using robot arm. In this project, the robot arm that carries the plotter at the end effector that serves as a tool to draw an alphabet such as ‘IIUM’ requires movement to the specific angle, position, speed and coordinates. In the thesis application, I have design a prototype of two degree of freedom plotter using robot arm that that use the Arduino software as a user interface and the data was sent to the hardware application board which is Arduino board by using serial communication cable to the robot arm servo. The experiment had been carried out to collect data and present it by using the graphical representation for each single movement of link one and link two. The unique of my project is the user can get the coordinates, position and angle easily by using the potentiometer that will be display on serial monitor. Following the advantages and limitation of this paper, some recommendations for future researchers were also presented.